More fast songs about the apocalypse [compact disc] - Moby (Mute Records, 2017)
As with much of Moby's output during his nearly three-decade-long career, a spiritual & political questioning underpins the nine songs comprising latest full length album. In characteristically iconoclastic fashion, the weighty themes explored here find expression as direct & personal music.